Formation of students’ creativity in the classroom of the Russian language - Jabborova, Dilbar (Linguistics and Culture Review, 2021)
This article discusses the formation of students’ creativity in a Russian language lesson in detail. Russian language teaching is carried out not only in literature classes, but also in any educational topic and outside the classroom, in free communication with students; live Russian is becoming a universal of school life. The basis for the formation of civic and cultural identity is the Russian language. Teaching is a complex, multi-component mobile system that is rebuilt depending on who needs to be taught what, for what. This is a system that requires the synthesis of all theoretical knowledge, the ability to analyze, and model the situation of communication in pedagogical practice.